2017
DOI: 10.1155/2017/3518402
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Manual Partial Red Cell Exchange in the Management of Severe Complications of Sickle Cell Disease in a Developing Country

Abstract: Introduction The realization of red cell exchange (RCE) in Africa faces the lack of blood, transfusion safety, and equipment. We evaluated its efficacy and safety in severe complications of sickle cell disease. Patients and Method Manual partial RCE was performed among sickle cell patients who had severe complications. Efficacy was evaluated by clinical evolution, blood count, and electrophoresis of hemoglobin. Safety was evaluated on adverse effects, infections, and alloimmunization. Results We performed 166 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…12,16,17 The objective of BT in SCD is not only correct chronic anemia but also to decrease HBS level and therefore to prevent or treat SCD complications whereas in case, of a simple or a transfusion exchange, either in an acute context or during a transfusion program. 3,6 Iterative transfusions are exposed to RCA, infectious and iron overload which pose a great risk of morbidity and mortality for SCD patients. 4,5 In this study, simple transfusion was performed in the majority of cases and few patients had a chronic transfusion program.…”
Section: Risk Factors Occurred Post-transfusion Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,16,17 The objective of BT in SCD is not only correct chronic anemia but also to decrease HBS level and therefore to prevent or treat SCD complications whereas in case, of a simple or a transfusion exchange, either in an acute context or during a transfusion program. 3,6 Iterative transfusions are exposed to RCA, infectious and iron overload which pose a great risk of morbidity and mortality for SCD patients. 4,5 In this study, simple transfusion was performed in the majority of cases and few patients had a chronic transfusion program.…”
Section: Risk Factors Occurred Post-transfusion Complicationsmentioning
confidence: 99%
“…3,4 It exists in three methods to treat SCD anemia: simple BT, punctual transfusion exchange, and longterm transfusion exchange. 5,6 Despite the benefits, multi-transfused patients are at an increased risk of complications of red cell alloimmunization, iron overload, and blood-transmitted infections. 7,8,9 The frequency of these complications correlates with RBCs units transfused.…”
mentioning
confidence: 99%
“…Exchange Blood transfusion has also been used in preventing SCD-related IP episodes. In general, blood exchange therapy was utilized after failure of other conservative measures such as aspiration, irrigation or injection of sympathomimetics 13,15,19,[22][23][24]26,28,34,37,39,46,49,53 . In a study including 10 SCD-related IP patients, exchange transfusion fully controlled priapic episodes in 50% of the patients.…”
Section: Data From Observational Studiesmentioning
confidence: 99%
“…Several studies demonstrated that blood exchange transfusion is safe 19,26,34,37 . ASPEN syndrome was not reported in most studies 19,22,26 but one study reported post-blood exchange mental confusion in 7 patients, which resolved several days after without any long-term sequalae 34 .…”
Section: Data From Observational Studiesmentioning
confidence: 99%
“…Data are sparse on the utility of RBC exchange for vaso‐occlusive pain crises. One group in a developing country noted that manual partial RBC exchange was tolerated and at least partially successful in reducing symptoms for both acute and chronic complications of SCD, including persistent vaso‐occlusive crises …”
Section: Indications For Rbc Exchangementioning
confidence: 99%